Access to complementary services under Ghana's Livelihood Empowerment Against Poverty programme in the Nadowli-Kaleo District. Issue 3 (3rd April 2023) - Sulemana, Mohammed; Fuseini, Moses Naiim; Shirazudeen, Biliguo
ABSTRACT: Livelihood Empowerment Against Poverty (LEAP), a social assistance programme, aims to reduce poverty and vulnerability. To this end, complementary services accompany such programmes to accelerate the process. However, a few studies have concentrated on access to complementary services. As such, this study focuses on investigating access to LEAP complementary services employing the mixed-methods design. Data were collected from 229 LEAP beneficiaries and LEAP programme implementers using questionnaires and an interview guide. The analysis of data involved descriptive statistics and thematic analysis. The study found that national health insurance (NHI), school feeding, the education capitation grant, and labour-intensive public works were the LEAP complementary services accessed although skewed to NHI. The barriers to access to complementary services included unavailability of services, ignorance of entitlement, inability to enforce the memorandum of understanding, and poor institutional coordination. To improve access to complementary services, sensitisation and enforcement of memorandum of understanding are vital.